Prosthetic management of a patient with Treacher Collins syndrome - Madhan R; Nayar Sanjna (Wolters Kluwer Medknow Publications, 2006)
Treacher Collins syndrome encompasses a group of closely related defects of the head and neck. It is a rare syndrome characterized by bilaterally symmetrical abnormalities derived from the first and second brachial arches and the nasal placode. It is an autosomal dominant disorder and its occurence ranges from 1 in 25,000 to 1 in 50,000 live births. The facial appearance of these patients can be improved by either surgical or prosthetic rehabilitation. In this case report we are presenting the features of a 13-year-old boy with Treacher Collins syndrome. A multidisplinary approach was followed in managing the situation. The various treatment options and the steps involved in making an auricular prosthesis are also discussed.